Mosque as a Bilingual Space – an Investigation on Speech Intelligibility in Mosque Acoustics Using Simulation Techniques - Elma ALIC; Asli OZCEVIK BILEN (Archives of Acoustics)
Mosques are Islamic places of worship where speech and music rituals are performed. Since two different languages are spoken there, mosques are described as bilingual spaces. Among studies on the complex acoustic structure of mosques there are only few studies on speech intelligibility and none on the bilingual characteristics of the mosque. Therefore, a comprehensive study has been carried out to evaluate the acoustic comfort of the contemporary Turkish mosques (CTM) over speech intelligibility of Turkish and Arabic languages. In the study the CTM model providing optimum acoustic conditions recommended in the literature is examined on speech intelligibility by applying acoustic simulation and auralisation techniques, as well as word recognition tests. As a result, the acoustic condition in the model is found insufficient in terms of speech intelligibility of both languages. Also, with the decrease of Signal-to-Noise Ratio (SNR), the Turkish intelligibility ratio is observed to decrease at least two times faster than the Arabic ones.